2019
DOI: 10.3390/app9193980
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition of Biochar Obtained from Agricultural Waste for Soil Amendment and Carbon Sequestration

Abstract: For an agricultural country such as Thailand, converting agricultural waste into biochar offers a potential solution to manage massive quantities of crop residues following harvest. This research studied the structure and chemical composition of biochar obtained from cassava rhizomes, cassava stems and corncobs, produced using a patented locally-manufactured biochar kiln using low-cost appropriate technology designed to be fabricated locally by farmers. The research found that cassava stems yielded the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 101 publications
(144 reference statements)
3
59
0
1
Order By: Relevance
“…The decrease in the bulk density of the biochar‐amended soil was accompanied by an increase in saturated volumetric water content (Usowicz et al., 2016). According to Wijitkosum and Jiwnok (2019), important properties of biochar are the high surface area and porosity, low bulk density, nutrient content, high stability, high CEC, neutral to high pH, and high carbon content. These properties make it suitable as an amendment for tropical sandy and clay soil in the northern area of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the bulk density of the biochar‐amended soil was accompanied by an increase in saturated volumetric water content (Usowicz et al., 2016). According to Wijitkosum and Jiwnok (2019), important properties of biochar are the high surface area and porosity, low bulk density, nutrient content, high stability, high CEC, neutral to high pH, and high carbon content. These properties make it suitable as an amendment for tropical sandy and clay soil in the northern area of China.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hardie, Clothier, Bound, Oliver, and Close (2014) indicated that the contribution of biochar porosity to soil pore volume was not observed consistently. Soil structure can be also improved by increased soil microbial biomass and enhanced microbial activity which reduces the soil bulk density (Ajayi et al., 2016; Ventura et al., 2012; Wijitkosum & Jiwnok, 2019). Our results suggest that the use of higher rates of biochar application (36 tons ha −1 ) results in a relatively low soil bulk density (Table 3), which is unfavorable for water storage.…”
Section: Discussionmentioning
confidence: 99%
“…Each feedstock source has a distinctive morphology which is retained in the biochar after carbonization. This image is taken from [ 29 ] from Applied Sciences Open Access journal MDPI publications.…”
Section: Figurementioning
confidence: 99%
“…Figure 2 here shows the honeycomb structure of biochar derived from different feedstocks like corncob, cassava rhizome and cassava stem [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar composition is highly heterogeneous. The major constituents are volatile matter, mineral matter (ash), adsorbed gases, and moisture [ 35 , 36 ]. In BC1, elements Ar, K, Ca, Zn, Rb, Sr and Ag were found.…”
Section: Resultsmentioning
confidence: 99%